Analisis Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Muhammad Syarifudin; Lutfi Baradja (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to examine and analyze the factors that influence earnings management. The research population is Mining Companies listed on the Indonesia Stock Exchange during 2019-2021. The type of data used is secondary data, namely data derived from financial reports and annual reports. The purposive sampling method used in this study obtained 43 samples and a total sample of 132 companies from 2019-2021. This study uses the Multiple Linear Regression model. The results of this study indicate that company size has a positive effect on earnings management, managerial ownership has a negative effect on earnings management and institutional ownership, profitability, liquidity and leverage have no effect on earnings management.